The value of commercial fish size distribution recorded at haul by haul compared to trip by trip. (18th September 2020) - Plet-Hansen, Kristian S; Bastardie, François; Ulrich, Clara
Abstract: Data from commercial fishing vessels may enhance the range of observations available for monitoring the marine environment. However, effort and catch data provide information on fish distribution with a bias due to spatial targeting and selectivity. Here, we measured the shortcomings of standard fishery-dependent data and advocate for the utilization of more precise datasets indirectly collected by the commercial fishery. Data from a Danish traceability system, which records size of commercial fish at the haul level, are held against the set-up of current eLog and sales slips' data collected for the Danish fisheries. We showed that the most accurate mapping of the spatial distribution of catches per size group is not only possible through size records collected at the haul level but also by high resolution on fishing effort data. In Europe, the regulation to land all catches with a quota or minimum size limit, including unwanted, has increased the focus on avoidance and discards; we show the potential of such data sources to inform on fish abundance and distribution, especially of importance where fishery-dependent data are the only source of information.